Network analysis of suicide ideation and depression–anxiety symptoms among Chinese adolescents - Yan Zhang; Jin Liu; Mei Huang; Liang Li; Yumeng Ju; Bangshan Liu; Shuyin Xu; Xiyu Wei; Wenwen Ou; Mohan Ma; Guanyi Lv; Xiaotian Zhao; et al. (General Psychiatry)
Background The co-occurrence of depression and anxiety among adolescents is typically associated with suicide ideation.Aims The study aimed to investigate the symptom-level relationship between suicide ideation and the comorbidity of depression and anxiety.Methods 1501 adolescents aged 12–19 years were assessed using the Patient Health Questionnaire (PHQ-9) and the Generalized Anxiety Disorder Scale, and 716 adolescents who scored ≥5 on both scales were selected as participants. Network analysis was used to identify the network structure of depressive symptoms and anxiety symptoms. Participants were categorised into either the suicide ideation or non-suicide ideation groups based on their scoring on the suicide-related item in PHQ-9. A comparison was made between the depression–anxiety symptom networks of the two groups.Results ‘Restlessness’, ‘sad mood’ and ‘trouble relaxing’ were the most prominent central symptoms in the depression–anxiety symptom network, and ‘restlessness’, ‘nervousness’ and ‘reduced movement’ were the bridge symptoms in this network. ‘Sad mood’ was found to be directly related to ‘suicide ideation’ with the highest variance. The network structure was significantly different in properties between the suicide ideation group and the non-suicide ideation group, with ‘restlessness’ and ‘sad mood’ exhibiting significantly higher influence in the network of the suicide ideation group than that in the non-suicide ideation group.Conclusion Restlessness and sad mood could be targeted for the intervention of depression–anxiety symptoms among adolescents with suicide ideation.